Rhetoric and Theology : the hermeneutic of Erasmus - Hoffman, Manfred, 1930- (Erasmus studies, 1993)
Departing from the traditional focus on Erasmus as philologist and moralist, Rhetoric and Theology shows how Erasmus attempted to interpret Scripture by way of a rhetorical theology that focuses on the figurative, metaphorical quality of language, with a view to moral and theological reform.